Respons Pemberian Coumarin Terhadap Produksi Mikro Tuber Planlet Kentang (Solanum tuberosum L.) Varietas Granola - Vivi Ulfia Hasni; Asil Barus; Ferry Ezra T. Sitepu; Rina Christina Br. Hutabarat (Jurnal Agroekoteknologi, 2014)
The objective of this experiment is to determine the response adding to the coumarin in to microtuber production of potato plantlets (Solanum tuberosum L.) varieties of granola. The research wasconducted at Tissue Culture Laboratory Experiment Berastagi where the surface level is atapproximately at ± 1340 m above sea level. The experiment was started on October 2013 untilFebruary 2014 using a completely randomized factorial design with two factors. The concentrations ofcoumarin was (0,000; 0,025; 0,050; and 0,075 gram/l) and the volume of coumarin was (30, 60, 90,120 ml). Parameters observed were the percentage of plantlets which produces micro tubers, thepercentage of plantlets were dead, the number of tubers on each micro planlet, the weight of tuberson each micro planlet, weight of each micro tuber, and diametres of tuber in each planlet. Theresults showed that adding of coumarin concentration into micro-tuber production of potatoplantlets was significantly affected the percentage of plantlets which produces micro tubers (1 BSAand 2 BSA) and the diameter of micro tubers of each plantlet. Adding of coumarin volume intomicro-tuber production of potato plantlets significantly affect on the percentage of plantlets whichproduces micro tubers (1 BSA and 2 BSA), the number of tubers on each micro planlet, the weightof tubers on each micro planlet, weight of each micro tuber, and diametres of tuber in each planlet.Key words : potatoes, production, micro tuber